A hybrid particle volume-of-fluid method for curvature estimation in multiphase flows. (April 2020) - Karnakov, Petr; Litvinov, Sergey; Koumoutsakos, Petros
Highlights: Hybrid method combining the volume-of-fluid with particles for curvature estimation. Method is shown to be more accurate for under-resolved interfaces compared to commonly used parabolic fitting. Method deployed also in broadly used software demonstrating that its capabilities are software independent. Excellent agreement found with experiments on bubble coalescence when using this method. Applicability to turbulent flows with bubbles is demonstrated. Abstract: We present a particle method for estimating the curvature of interfaces in volume-of-fluid simulations of multiphase flows. The method is well suited for under-resolved interfaces, and it is shown to be more accurate than the parabolic fitting that is employed in such cases. The curvature is computed from the equilibrium positions of particles constrained to circular arcs and attracted to the interface. The proposed particle method is combined with the method of height functions at higher resolutions, and it is shown to outperform the current combinations of height functions and parabolic fitting. The algorithm is conceptually simple and straightforward to implement on new and existing software frameworks for multiphase flow simulations thus enhancing their capabilities in challenging flow problems. We evaluate the proposed hybrid method on a number of two- and three-dimensional benchmark flow problems and illustrate its capabilities on simulations of flows involving bubble coalescence and turbulent multiphase flows.